Tracking Strategy in an Entrepreneurial Firm - Mintzberg, Henry; Waters, James A. (Academy of Management Journal, 1982)
This study tracks the strategies of a retail chain over 60 years of its history to show how that vague concept called strategy can be operationalized and to draw conclusions about strategy formation in the entrepreneurial firm that grows large and formalizes its structure. The conclusions focus on patterns of strategic change and on contrasting characteristics of entrepreneurship and planning.